Kontribusi Pajak Hotel Dan Restoran Sebelum Dan Sesudah Pandemi Covid 19 Terhadap Pendapatan Asli Daerah (PAD) Kabupaten Lombok Barat - Hadi, Sulhan; Eikman, Alfian; Amil, Amil (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This research is about the impact of the Covid 19 container on hotel and restaurant tax receipts in West Lombok Regency. West Lombok Regency is a Regency that relies heavily on the tourism sector as a mainstay sector in terms of receiving regional income after the agricultural sector. In this study, the authors found that the tax contribution from the hotel and restaurant sector is the largest contributor to PAD (Regional Original Income) compared to other sectors. However, in 2020 where the Corona virus has been detected in Indonesia and Lombok Island in particular, revenue from this sector has decreased significantly. In the future, the West Lombok Regency Government should be able to look for other sources of income and not be too dependent on tourism, because according to the findings of researchers the nature of the tourism sector is very sensitive to various issues such as security and comfort issues, even a few security issues are not good then will immediately make the tourism sector hit. If we look at the past four years, the tourism sector on the island of Lombok has twice been hit hard, the first in 2018 an earthquake that paralyzed this sector, the second in 2020 due to the Corona virus, government efforts need to be made West Lombok Regency to seek new tax receipts other than hotels and restaurants.This research is about the impact of the Covid 19 container on hotel and restaurant tax receipts in West Lombok Regency. West Lombok Regency is a Regency that relies heavily on the tourism sector as a mainstay sector in terms of receiving regional income after the agricultural sector. In this study, the authors found that the tax contribution from the hotel and restaurant sector is the largest contributor to PAD (Regional Original Income) compared to other sectors. However, in 2020 where the Corona virus has been detected in Indonesia and Lombok Island in particular, revenue from this sector has decreased significantly. In the future, the West Lombok Regency Government should be able to look for other sources of income and not be too dependent on tourism, because according to the findings of researchers the nature of the tourism sector is very sensitive to various issues such as security and comfort issues, even a few security issues are not good then will immediately make the tourism sector hit. If we look at the past four years, the tourism sector on the island of Lombok has twice been hit hard, the first in 2018 an earthquake that paralyzed this sector, the second in 2020 due to the Corona virus, government efforts need to be made West Lombok Regency to seek new tax receipts other than hotels and restaurants.